2013
DOI: 10.4172/2161-1068.1000140
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tuberculous Drugs and Susceptibility Testing Methods: Current Knowledge and Future Challenges

Abstract: The emergence of multi-drug resistant tuberculosis (MDR-TB) outbreaks during 1990s and more recently the highly lethal strains of extensively drug-resistant TB (XDR-TB) is hampering efforts to control and manage tuberculosis (TB), and also threatening World Health Organization's target of TB elimination by 2050. The TB community has promoted a full pipeline of candidate for the new TB drugs at all phases of development. The majority of candidates are in preclinical and early clinical development. The challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In addition to its high accuracy, its main advantages are: it is used in a classic LJ medium, with which TB laboratories are already familiar; no additional equipment is required; and it is faster than PM using LJ. In this study, most of the technicians who performed the tests found the kit less laborious than PM using LJ, and its results easier to interpret, based on color change, which is another positive aspect of the method [24,19]. These features make it suitable for use in laboratories in low and middle income countries; however, biosafety procedures need to be maintained due to the risk of aerosol production during handling.…”
Section: Discussionmentioning
confidence: 89%
“…In addition to its high accuracy, its main advantages are: it is used in a classic LJ medium, with which TB laboratories are already familiar; no additional equipment is required; and it is faster than PM using LJ. In this study, most of the technicians who performed the tests found the kit less laborious than PM using LJ, and its results easier to interpret, based on color change, which is another positive aspect of the method [24,19]. These features make it suitable for use in laboratories in low and middle income countries; however, biosafety procedures need to be maintained due to the risk of aerosol production during handling.…”
Section: Discussionmentioning
confidence: 89%
“…DHR is an unpredictable reaction and it refers to an immunologically mediated hypersensitivity reaction. It may be either immunoglobulin E (IgE) mediated or non-IgE mediated, immediate or delayed hypersensitivity reaction [7][8][9]. DHR may be mild, life threatening, it is a challenge for the physicians.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Clinically, the most advanced regimen [25,26] in this category is known as PaMZ, a combination of the novel nitroimidazo-oxazine PA-824, moxifloxacin, and pyrazinamide. [27] The REMoxTB trial [28] replaced either H or E with moxifloxacin (M) in two experimental, 4 months experimental regimens (2HRZM/2HRM and 2MRZE/2MR). This regimen has the potential not only to shorten the duration of first-line treatment, but also to treat a proportion of patients who would previously have needed second-line treatment-i.e., patients with MDR-TB.…”
Section: Introductionmentioning
confidence: 99%